THE INFLUENCE OF BRAND IMAGE ON PRODUCT QUALITY AND PRICE TO PURCHASE DECISIONS BELLA SQUARE SQUARE HIJAB FOR FEMALE STUDENTS FACULTY OF ECONOMICS AND BUSINESS UNIVERSITY MALIKUSSALEH - Cut Nurul Azman; Halida Bahri; Jullimursyida; Adnan (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2024)
This study aims to determine the influence of brand image, product quality, and price on purchase decisions for Bella Square Hijab among students of the Faculty of Economics and Business, Malikussaleh University. The research method used in this study is quantitative. The instruments in this study include validity tests, reliability tests, and classical assumption tests, namely normality tests, multicollinearity tests, and heteroscedasticity tests. This study was conducted on female students of the Faculty of Economics and Business, Malikussaleh University, who had used and made purchases of the Bella Square Hijab. The primary data were obtained by distributing questionnaires via Google Forms to 100 respondents. The data analysis technique employed was multiple linear regression analysis with the help of SPSS. The results indicate that brand image does not significantly affect purchase decisions for Bella Square Hijab. Product quality significantly influences purchase decisions for Bella Square Hijab, and price does not have a significant effect on purchase decisions for Bella Square Hijab. The practical implication of this study is that Bella Square Hijab producers need to improve their brand image, product quality, and price to increase sales.